Written expression and school achievement of young school-age students - Vasiljević, Nada (Norma, 2023)
The process of literacy of students in primary school is complex, pedagogically relevant and socially significant. In order for students to learn correct oral and written expression, it is necessary to work persistently and continuously with them. A student's literacy can only be the result of long, gradual and systematic learning and practice. The development of the culture of expression and literacy should be constantly encouraged with students from the very beginning of school. The aim of this research was to verify whether and to what extent there is a significant statistical connection between written expression and school success of students in the second triad of elementary school. The research was conducted on a sample of 109 elementary school students in the territory of Banja Luka. For the purpose of this research, the Vocabulary Test was applied.
Keywords: students; younger school age; teacher; written expression; school success of students